Analisis Motivasi Belajar Siswa pada Pembelajaran IPA di MAS Darul Ulum Banda Aceh - Syah Mudra, M Deva; Shalihah, Nadiyatun; Ramdhani, Alia; Afrida, Juniar (Intelektualita: Journal of Education Sciences and Teacher Training, 2024)
This study aims to analyze students learning motivation in the Science (IPA) subjects at MAS Darul Ulum Banda Aceh. Qualitative descriptive approach was employed, involving 15 IPA students selected through stratified random sampling. Data were collected through interviews and direct observations of the teaching and learning activities. The findings reveal that students motivation is influenced by internal and external factors. Internal factors, such as interest, curiosity, and personal goals, play a significant role in enhancing students motivation. External factors, including parental encouragement, peer support, and the social environment, also contribute substantially to their learning motivation. Major challenge identified was students' lack of interest in IPA, as they perceive it as irrelevant to their future educational and career goals. The teacher's influence was found to be crucial, particularly when employing interactive teaching methods like practical activities and out-of-class experiences, which effectively increase students' engagement and understanding of IPA. Furthermore, a conducive classroom environment also plays a role in motivating students, although individual characteristics influence how much students are affected by their surroundings. The study suggests that MAS Darul Ulum should adopt varied, experience-based teaching approaches and consider classroom dynamics in educational policies to enhance students' motivation and overall learning outcomes.